2015
DOI: 10.1155/2015/909016
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological and Agronomic Potential of Endophytic Pink-Pigmented MethylotrophicMethylobacteriumspp.

Abstract: The genus Methylobacterium is composed of pink-pigmented facultative methylotrophic (PPFM) bacteria, which are able to synthesize carotenoids and grow on reduced organic compounds containing one carbon (C1), such as methanol and methylamine. Due to their high phenotypic plasticity, these bacteria are able to colonize different habitats, such as soil, water, and sediment, and different host plants as both endophytes and epiphytes. In plant colonization, the frequency and distribution may be influenced by plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 140 publications
(230 reference statements)
5
74
0
3
Order By: Relevance
“…Which was previously reported by other authors (Sy et al, 2001;Madhaiyan et al, 2006Madhaiyan et al, , 2007Bogas et al, 2016). The mechanisms involved are: (1) phytohormone production: Mainly auxin and cytokinines (Dourado et al, 2015;Kwak et al 2014); (2) Stress decrease: Heavy metal tolerance (Dourado et al, 2015) and ACC deaminase production (Bogas et al, 2016). Bacterial ACC deaminase uses the ethylene precursor: ACC (Aminocyclopropane-1-carboxylic acid) as source of nitrogen, decreasing the production of ethylene, increasing plant growth (Hardoim et al, 2008(Hardoim et al, , 2015; (3) Nutrient uptake: Phosphate solubilization (Glick, 1995), nitrogen fixation and plant nodulation (Sy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Which was previously reported by other authors (Sy et al, 2001;Madhaiyan et al, 2006Madhaiyan et al, , 2007Bogas et al, 2016). The mechanisms involved are: (1) phytohormone production: Mainly auxin and cytokinines (Dourado et al, 2015;Kwak et al 2014); (2) Stress decrease: Heavy metal tolerance (Dourado et al, 2015) and ACC deaminase production (Bogas et al, 2016). Bacterial ACC deaminase uses the ethylene precursor: ACC (Aminocyclopropane-1-carboxylic acid) as source of nitrogen, decreasing the production of ethylene, increasing plant growth (Hardoim et al, 2008(Hardoim et al, , 2015; (3) Nutrient uptake: Phosphate solubilization (Glick, 1995), nitrogen fixation and plant nodulation (Sy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…has been isolated from several plant species (Omer et al, 2004), actively colonizing the leaf surface or the inner plant tissues, such as soybean, sugarcane, cotton, citrus, eucalyptus, bamboo, Catharanthus roseus, tobacco, strawberry, mangrove plants and different Fabaceae species (Madhaiyan and Poonguzhali, 2014;Dourado et al, 2015). Inside the host plant Rhizobium and Methylobacterium could produce phythormones (IAA and citokinine) or interact with the microbial community (endophytes and pathogens) (Madhaiyan et al, 2006;Dourado et al, 2015;Azevedo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Dourado et al (2015) found that the community of Methylobacterium spp. that was associated endophytically to 6 plant hosts was able to fix atmospheric nitrogen, solubilize phosphate, produce phytohormones, extracellular enzymes and promote the biocontrol of pathogens and induce systemic resistance.…”
Section: Endophytic and Epiphytic Ppfms Associated With Sugarcanementioning
confidence: 99%
“…The PPFMs were reported to distribute ubiquitously in association with many plant species either epiphytically or endophytically (Dourado et al, 2012). In addition, some authors demonstrated that members of this group harbor a strong symbiotic interaction with the plant, showing an ability to promote its growth (Chistoserdova et al, 2003), by direct ways related to nutrient availability or phytohormones production or by indirect ways inducing systemic resistance to plants and controlling pathogens (Dourado et al, 2015). For example, Methylobacterium nodulans (Sy et al, 2001;Jourand et al, 2005) and Methylobacterium sp.…”
Section: Introductionmentioning
confidence: 99%
“…A praça é uma forma com usufruto e com funções que identificam a cidade e seus modos de vida e demonstram a dinâmica da vida no espaço urbano que a rodeia (LAMAS, 2004;DOURADO;SILVA, 2005).…”
Section: A Praça No Brasilunclassified